El molino del diablo. Tiempo y poder a partir de Pierre Bourdieu - Cristiano, Javier Luis (Res Publica. Revista de Historia de las Ideas Políticas, 2022)
The article aims to establish, based on a systematic reading of the work of Pierre Bourdieu, some conceptual relationships between power and the social constitution of time. Starting from the assumption that time, the way in which we experience, conceive and use it, is a social construction, we try to identify some of the ways in which power intervenes in these construction processes, a task for which the work of Bourdieu is not only strategic but unavoidable, as it is among the few that have dealt in depth with both issues. The article first identifies the general coordinates of Bourd's treatment of both questions, differentiating five dimensions of social time: time as practical experience, as resource, as structural constraint, as representation of the past and future, and as existential tension. In each one, then, concrete relationships between power and time are elaborated, which are passed in clean form globally in the conclusions.
Keywords: Social Time; Power; Inequality; Struggles; Practices